2013
DOI: 10.2135/cropsci2013.01.0043
|View full text |Cite
|
Sign up to set email alerts
|

Is the Stay‐Green Trait in Sorghum a Result of Transpiration Sensitivity to Either Soil Drying or Vapor Pressure Deficit?

Abstract: Persistence of green leaves during seed fill, referred to as a stay‐green trait, has been investigated in sorghum [Sorghum bicolor (L.) Moench] as an approach to increasing yields under water‐limited conditions. An hypothesis to explain the observation of stay green in some sorghum genotypes and not in others is that the genotypes expressing the trait employ mechanisms to increase availability of soil water during seed fill. In this study, the expression of two mechanisms resulting in soil water conservation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 17 publications
3
24
0
Order By: Relevance
“…The light flux 450-500 l mol m -2 s -1 was maintained above the canopy level. The TR subjected to increasing VPD was measured as described in the earlier studies in sorghum by Gholipoor et al (2010), Choudhary et al (2013) and Shekoofa et al (2014). During the transition time, the pots are measured by a gravimetric method using 0.01 precision balances (FBK, Kern & Sohn GmbH, Balingen, Germany).…”
Section: The Response Of Tr To Evaporative Increasing Vpdmentioning
confidence: 99%
See 1 more Smart Citation
“…The light flux 450-500 l mol m -2 s -1 was maintained above the canopy level. The TR subjected to increasing VPD was measured as described in the earlier studies in sorghum by Gholipoor et al (2010), Choudhary et al (2013) and Shekoofa et al (2014). During the transition time, the pots are measured by a gravimetric method using 0.01 precision balances (FBK, Kern & Sohn GmbH, Balingen, Germany).…”
Section: The Response Of Tr To Evaporative Increasing Vpdmentioning
confidence: 99%
“…First of these mechanisms is the expression of a limited transpiration rate under increasing vapour pressure deficit (VPD) conditions and the second is a decrease in transpiration at high soil moisture conditions when subjected to progressive soil drying conditions. These two mechanisms were first studied in a few genotypes of sorghum (Gholipoor et al 2012;Choudhary et al 2013), where significant genetic variation was found among the genotypes. This phenomenon was also experimented in a series of crops by several researchers and existence of genetic variation for transpiration rate at different vapor pressure deficit levels (Fletcher et al 2007;Devi et al 2010;Kholova et al 2010;Gilbert et al 2011;Zaman-Allah et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The stay-green drought adaptation trait has been a focus of sorghum crop improvement programmes in Australia and the USA for over 30 yr (Rosenow, 1977;Henzell et al, 1992;Jordan et al, 2012). The physiological basis of stay-green remains unclear, although a number of studies in sorghum have increased our understanding of this complex trait (Borrell et al, 2000a,b;Harris et al, 2007;van Oosterom et al, 2011;Vadez et al, 2011;Jordan et al, 2012;Burke et al, 2013;Choudhary et al, 2013). Earlier research focused on the nitrogen status of plants during terminal water deficit (Borrell & Hammer, 2000;Borrell et al, 2001), but later studies also evaluated the role of plant water management (Hammer, 2006;Vadez et al, 2011;Choudhary et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One approach to achieve water conservation is to have TR lim under high atmospheric VPD as a result of partial closure of stomata. Partial stomatal closure would occur when water transfer to guard cells cannot match the transpiration rate (TR) that results from fully open stomata (Brodribb and Jordan, 2008; Yang et al, 2012; Shekoofa et al, 2013; Choudhary et al, 2013). A simulation study of maize production in the US (Messina et al, 2015) illustrated the regions and probability of yield increase that could be expected from the TR lim trait.…”
mentioning
confidence: 99%